INTEGRATION OF LEAN AND GREEN MANUFACTURING TO SUSTAINABILITY IMPROVING AT PT. TEXTILE JAYA GEMILANG - Rony Prabowo (UNIPA PRESS, 2019)
Textile Jaya Gemilang is a textile company that has a cotton fabric finishing unit. In the identification carried out the company still produces waste and has not yet carried out an environmentally friendly process. Therefore efforts are needed to identify waste in the process of finishing woven fabrics to make the process environmentally friendly by considering the level of eco efficiency and eco costs to determine the proposed process that is environmentally friendly. This research includes steps such as analyzing value stream mapping to find out activities that have value added and categorized as NVA. Furthermore, measurements of environmental impacts were carried out with LCA (Life Cycle Analyzing) and then gave a proposal to provide a proposed process with the 6R approach (reuse, reduce, recycle, remanufacturing, recovery and redesign) in the process of finishing cotton cloth obtained by waste, namely in appropriate processing, defect and waiting time . The results of the Life Cycle Assessment showed results for a process of 248.76 pt, for Life Cycle Impact Assessment Damage Category Human Health of 4.8813 DAILY, Damage Category Ecosystem Quality of 310,000 PDF * m2yr and for Damage Category Resources 1615,646 MJ surplus . Eco cost is Rp. 608,425,018.2. Proposed environmentally friendly process by raising the level of green manufacturing to recycling and reuse.